Illustrated key for the identification of the known zoeal stages of brachyuran crabs (Crustacea: Decapoda) from tropical and subtropical Brazil, southwestern Atlantic - Koettker, Andrea G.; Sumida, Paulo Y.g.; Lopes, Rubens M.; Freire, Andrea S. (Zootaxa, 2012)
Approximately 370 brachyuran species have so far been recorded from the Brazilian coast, 123 of which have had theirlarval stages fully or partially described. The pictorial guide allows the identification of the first zoea of 110 species. Theremaining 13 species with known larval stages are treated to the genus level because of difficulties in the morphological differentiation of closely related species.